Frammenti di Napoli Naples and its fragments - Maria Ines Pascariello (UrbsHistoriaeImago. Storia e immagine dei territori, dei centri urbani e delle architetture, 2018)
This work intends to collect the results of studies and researches which contribute to strengthening the knowledge of the area and in documenting all these shades that converge on qualifying in a cultural entity as collective heritage: the single heritages, through knowledge can obtain in this way not only an adequate representation. It is thus not by chance, that this book is dedicated to the city of Naples, a city with a strong and complex identity, with classical roots, full of conflict and eager to confrontations; the artistic and cultural heritage that this city preserves, almost a catalogue of the entire Mediterranean civilization, of which it is the symbol, is made of great testimonies, but also of small fragments, of layers and mixtures, which together converge on the culture of 'making a system' aimed at the creation of a territory network, at the bringing closer and understanding of single cultural identities, at a best mutual perception.